If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = -2x + 8(x + 3) Reorder the terms: -6 = -2x + 8(3 + x) -6 = -2x + (3 * 8 + x * 8) -6 = -2x + (24 + 8x) Reorder the terms: -6 = 24 + -2x + 8x Combine like terms: -2x + 8x = 6x -6 = 24 + 6x Solving -6 = 24 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + -6x = 24 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + -6x = 24 + 0 -6 + -6x = 24 Add '6' to each side of the equation. -6 + 6 + -6x = 24 + 6 Combine like terms: -6 + 6 = 0 0 + -6x = 24 + 6 -6x = 24 + 6 Combine like terms: 24 + 6 = 30 -6x = 30 Divide each side by '-6'. x = -5 Simplifying x = -5
| 2+(-8)=p | | 2x-5=2+6 | | 15x-7=4y+3 | | n-6=2+2n | | 15r^3-6r^2+5r-2=0 | | i-61=13 | | 5x+15=39 | | 9a+3b=8 | | x-46=28 | | 4n+17+3n+23=180 | | x+5.3=7.5 | | 2-17=-7 | | 4n-1.9=2.5 | | e+f=g | | 2z-5(2+3)=3z+1 | | w-67=64 | | y^4+10y^2+24=0 | | -8.4x=0.294 | | 4sin^2(2x)=2 | | x+2x+8=42 | | k-76=42 | | f-8=16 | | -.0002+.00002= | | 2x+8+(90+x)=180 | | 16k^2-24k+9=0 | | 5x-105= | | c-78=60 | | -14m-14=46 | | 4*(10*5)=(4*10)*n | | 8y+9=8y-5 | | 2z-2=3a+3 | | C^2(3c+a)-a(3c+a)= |